2020
DOI: 10.1155/2020/6541761
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like-Receptor Gene Polymorphisms in Tunisian Endemic Pemphigus Foliaceus

Abstract: Pemphigus foliaceus (PF) is considered to be caused by the combined effects of susceptibility genes and environmental triggers. The polymorphisms of Toll-like receptors (TLRs) genes have been associated with the risk of various autoimmune diseases. The aim of this study was to evaluate the potential association of TLR2-3-4 and 7 gene polymorphisms with Tunisian PF. Fourteen polymorphisms were analyzed in 93 Tunisian PF patients compared to 193 matched healthy controls: rs5743703-rs5743709 and (GT)n repeat (TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…Indeed, these mid‐sized GT repeats are the most abundant in every population (Yim et al., 2004). Association of the genotype GT18/GT19 with SLE susceptibility is in line with a recent study conducted in our laboratory, showing that the GT18 allele and the GT18/GT19 genotype are associated with a significant risk to Pemphigus Foliaceus auto‐immune disease ( p = 0.02 and p = 2.3 × 10 −4 , respectively) (Abida et al., 2020).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Indeed, these mid‐sized GT repeats are the most abundant in every population (Yim et al., 2004). Association of the genotype GT18/GT19 with SLE susceptibility is in line with a recent study conducted in our laboratory, showing that the GT18 allele and the GT18/GT19 genotype are associated with a significant risk to Pemphigus Foliaceus auto‐immune disease ( p = 0.02 and p = 2.3 × 10 −4 , respectively) (Abida et al., 2020).…”
Section: Discussionsupporting
confidence: 85%
“…PCR reactions were performed in a total volume of 25 μl containing enzymes at 1× buffer, 0.2–0.4 μmol of each primer (Invitrogen, CA, USA), 0.12 mMdNTP (Invitrogen, CA, USA),1 U Taq polymerase (Invitrogen, CA, USA), and 50 ng genomic DNA. The amplified PCR products were digested with specific restriction enzymes at their optimum temperature (Abida et al., 2020; Karananou et al., 2019). Then, the digested products were visualized by electrophoresis on a 3% agarose gel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined in detail the 120 informative women (70 HC and 50 PF heterozygotes for AR gene). TLR7 and FOXP3 genotypes were described in our previous data (Abida et al, 2020 ; Ben Jmaa et al, 2017 ). Overall, our results showed that the preferential XCI skewed profile correlated with the heterozygote frequency distribution of those immunity‐related genes in PF patients in comparison to their matched HC (Table 4 ).…”
Section: Resultsmentioning
confidence: 97%
“…Our previous study reported significant associations of genetic variants of other X‐linked genes like the FOXP3 gene (Xp11.23) with the risk for PF (Ben Jmaa et al, 2017 ). Concerning the TLR7 gene mapped in Xp22.3, we have noted an increase in the TLR7 rs3853839 > GG functional polymorphism in patients with PF compared to HC (Abida et al, 2020 ). Our results showed evidence of increasingly skewed and extremely skewed patterns among heterozygote patients in comparison to their matched HC in AR , TLR7 , and FOXP3 gene polymorphisms were shown.…”
Section: Discussionmentioning
confidence: 93%